Star Trek : the art of Juan Ortiz - Ortiz, Juan (Juan M.) (London : Titan Books, 2013)
Unique retro designs depicting classic episodes of Star Trek: The Original Series, captivating not only Trek fans but lovers of all sci-fi!.
Includes index.
Keywords: Ortiz, Juan; Star trek (Television program) -- Art; Art